STRATEGI PENGELOLAAN PERUBAHAN APBDESA KALURAHAN CATURTUNGGAL TAHUN 2020 BIDANG PENANGGULANGAN BENCANA DARURAT - Agus Santoso; Mohamad Mahsun (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
APBDesa budget changes which changes 4 (four) fields in the APBDesa, namely the field of village government, community development, empowerment and village development, turns into 5 (five) fields with the addition of the field of emergency disaster management, which is new and urgent. In addition, it also requires precision in its management. So, this research is important to know about its management strategy. The purpose of this study was to determine the Strategy for Management of Changes in the Village Budget of Caturtunggal Village in 2020 in the Field of Emergency Disaster Management. The research method used is descriptive qualitative research method. In this qualitative research, the SWOT analysis method is also used, which includes identification of the internal and external environment, identification of strategies through SWOT analysis, and formulating strategies to manage changes in the APBDes of Caturtunggal Village. After knowing the SWOT Analysis matrix, then through the Village Consultative Meeting the budget for the Emergency Disaster Management Sector is Rp. 3,756,300,000.00 from the APBDesa budget changes of Rp. 11,878,935.850.00. In which, the budget is used for routine coordination, formation of health volunteer cadres, distribution of financial assistance and life insurance, purchasing goods for Covid-19 prevention assistance, establishing the Covid-19 Task Force, food assistance, socialization and education, optimizing the hamlet Covid-19 Task Force, optimizing village facilities, and optimizing task force posts.